Development of Integrated Case-Based Learning Science Modules on Coconut Shell Waste Management to Improve Science Literacy - Sri Wahyuni; Siti Shofa Assyifa'ul Qulbi Barid; Arvidhea Safira Gunawan; Desi Ummi Rusdiana; Himatus Sya'adah (FKIP Universitas Lampung, 2026)
Science learning emphasizes not only conceptual understanding but also real- world relevance. A case-based learning approach allows students to explore contextual problems. Therefore, this study develops a science learning module based on case-based learning, integrated with the utilization of coconut shell waste. This study used a Research and Development approach and implementing ADDIE instructional design model. The trial of the learning implementation involved 27 students from class VII E at SMPN 2 Panti. Data collection techniques included expert validation sheets, observation sheets for learning implementation, student response questionnaires, and cognitive tests using a one-group pretest-posttest design. The validity test results showed that the developed module achieved an average score of 92% and was rated as very valid, indicating that it met the standards for truth in content, language, presentation, graphics, and the components of scientific literacy indicators. Furthermore, the practicality test, based on observation sheets from eight meetings, produced an average score of 87% (very practical). Regarding the effectiveness evaluation, because this study used a one-group control design, the findings are interpreted with caution and are not conclusive evidence of an increase in students' scientific literacy. The indicators for explaining scientific phenomena and interpreting scientific data achieved an N-gain of 0.7 (high), while the indicator for designing scientific investigations achieved an N-gain of 0.5 (moderate). The statistical analysis showed a significant difference between the pre-test (27.00) and post-test (73.40) scores. The paired-samples T-Test results, t(26) = 16.84, p < 0.001, indicate a significant change in scores after the intervention. The average N-gain score was 0.6, which was included in the moderate range. A positive acceptance rate was also evident in the student response questionnaire, with a 81% score. Based on all results, it was concluded that this integrated local potential learning module improves students' scientific literacy. Keywords: case-based learning, coconut shell waste, local potential, science module, scientific literacy.